2023
DOI: 10.1186/s12974-023-02961-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia combined with extracellular vesicles from clonally expanded immortalized mesenchymal stromal cells improves neurodevelopmental impairment in neonatal hypoxic-ischemic brain injury

Nicole Labusek,
Parnian Ghari,
Yanis Mouloud
et al.

Abstract: Background Neonatal encephalopathy following hypoxia–ischemia (HI) is a leading cause of childhood death and morbidity. Hypothermia (HT), the only available but obligatory therapy is limited due to a short therapeutic window and limited efficacy. An adjuvant therapy overcoming limitations of HT is still missing. Mesenchymal stromal cell (MSC)-derived extracellular vesicles (EVs) have shown promising therapeutic effects in various brain injury models. Challenges associated with MSCs’ heterogenei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…A functional composite scaffold composed of heparin, collagen, and VEGF in which the composite scaffold has good mechanical properties and is able to control the rate of VEGF release may be a viable treatment for SCI. According to the study conducted by M. Dzietko et al, it was shown that VEGF has a dual role in facilitating angiogenesis and safeguarding neurons following brain damage ( Labusek et al, 2023 ). Hence, through the incorporation of various growth factors into the material scaffolds, these scaffolds serve the dual purpose of immobilizing and preserving the activity of the growth factors.…”
Section: Combined Application Of Biomaterialsmentioning
confidence: 99%
“…A functional composite scaffold composed of heparin, collagen, and VEGF in which the composite scaffold has good mechanical properties and is able to control the rate of VEGF release may be a viable treatment for SCI. According to the study conducted by M. Dzietko et al, it was shown that VEGF has a dual role in facilitating angiogenesis and safeguarding neurons following brain damage ( Labusek et al, 2023 ). Hence, through the incorporation of various growth factors into the material scaffolds, these scaffolds serve the dual purpose of immobilizing and preserving the activity of the growth factors.…”
Section: Combined Application Of Biomaterialsmentioning
confidence: 99%